An annotated checklist of the chondrichthyans of Taiwan - Ebert, David A.; White, William T.; Ho, Hsuan-Ching; Last, Peter R.; Nakaya, Kazuhiro; Séret, Bernard; Straube, Nicolas; Naylor, Gavin J.p.; de Carvalho, Marcelo R. (Zootaxa, 2013)
An annotated checklist of chondrichthyan fishes (sharks, batoids, and chimaeras) occurring in Taiwanese waters is presented. The checklist is the result of a biodiversity workshop held in Mach 2012 as well as on-going systematic revisions by the authors. The chondrichthyan fauna of Taiwan is one of the richest in the world with the number of species totaling 181, comprising 52 families and 98 genera. It includes 31 families, 64 genera, and 119 species of sharks, 19 families, 31 genera, and 58 species of batoids, and 2 families, 3 genera, and 4 species of chimaeras. The most species-rich families are the Carcharhinidae with 22 species followed by the Scyliorhinidae with 17. The most species-rich batoid families are the Dasyatidae with 11 species and and the Rajidae with 10. Verified voucher materialis provided for each species where available and potential taxonomic issues are high-lighted when applicable. This represents the first detailed, evidence-based checklist of chondrichthyans from Taiwanese waters in over 40 years.